Improving Thermal Performance of Rammed Earth Walls Using Expanded Granulated Cork - Correia-da-Silva, J. J. (2014)
The use of soil construction dates back to the beginning of our civilization. In the South of Portugal there is still a large number of buildings with rammed earth walls, but this technology has been falling into disuse since the middle of last century. The earth construction is highly sustainable since earth is a local material and is 100% reusable. The buildings with rammed earth walls have a high thermal inertia which, given the climate characteristics Portugal, enjoys its thermal behavior. However, it is desirable that the thermal conductivity of the rammed earth were lower. Environmental concerns related to energy consumption associated with comfort in housing and construction, transportation and application of materials used in construction, has led us to seek new solutions in building typologies on earth. Considering these aspects and aiming to improve the energy efficiency in buildings with rammed earth walls, this paper presents the results of tests performed in laboratory to characterize phisical properties of several compositions containing soil and expanded granulated cork. Compositions were considered soil and expanded granulated cork having the following percentages of expanded granulated cork, 0%, 10%, 15%, 20% and 25%. In order to characterize the different compositions from the point of view of mechanical and thermal performance, cubes were produced with 10 centimeters edge and assayed in order to calculate its compression resistance and its thermal conductivity. The results showed that the use of this type of building typologies on earth with the incorporation of expanded granulated cork allows to increase your performance by making it possible to adapt this typology needs of today, including the demands of the Portuguese legislation. The results of this research can be applied, with the appropriate adaptations, both in buildings in rammed earth and in buildings in adobe.